PENGARUH RETURN ON EQUITY DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM - Putiarani, Anggita Tania (COMPETITIVE, 2023)
An investor should consider what things affect the rate of return of the stock before investing. Therefore, this research intends to see whether there is an influence between Return On Equity and Debt to Equity Ratio on the stock return of the sample companies. Purposive Sampling method was used in determining the sample with several criteria and getting 35 samples from the selected Food and Beverages Company. This research takes data from the Indonesian stock exchange. Stock Return is positively influenced by ROE and not influenced by DER, this result is shown from the Partial Test (t test). ROE and DER have a simultaneous effect on Stock Return, this is indicated by the simultaneous test (f test).